2020
DOI: 10.1111/ijfs.14814
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of extracts from peels and stems of yellow‐fleshed and white cassava varieties

Abstract: This study focused on the exploration of the potentials of extracting antioxidants from peels and stems of yellow-fleshed and white cassava varieties. The effect of particle size (0.2 and 0.5 mm) and variety on the phenolic content and antioxidant activity was assessed. The peels of the yellow-fleshed cassava variety with a particle size of 0.2 mm showed the highest phenolic content with 681.5 GAE mg 100 g −1 and antioxidant activity of 19% and 425 μM TE g −1 dry matter using DPPH and FRAP assays respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Despite coming from the same type of plant, antioxidants in cassava leaves and peel had different levels. Similar results have also been reported by Ekeledo et al [76], who found that yellow cassava peel extract had higher scavenging activity than cassava stem extract. Gonçalves et al [77] also found differences in antioxidant activity in the leaves, seeds, pulp, and peel of Chamaerops humilis L. These differences could be caused by alterations in the structure of the phenolic components in plants due to variations in cell structure and chemical substances in plant tissues.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…Despite coming from the same type of plant, antioxidants in cassava leaves and peel had different levels. Similar results have also been reported by Ekeledo et al [76], who found that yellow cassava peel extract had higher scavenging activity than cassava stem extract. Gonçalves et al [77] also found differences in antioxidant activity in the leaves, seeds, pulp, and peel of Chamaerops humilis L. These differences could be caused by alterations in the structure of the phenolic components in plants due to variations in cell structure and chemical substances in plant tissues.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…The highest total phenols extracted was 0.23 mg/g at 140°C while the least was at 200 °C. These values were much lower than the 2 mg/g reported by Ekeledo et al, 2021 in white peel cassava after treatment with 80% methanol at ambient temperature. The total phenols in our untreated sample (RT) is still lower than the value reported by Ekeledo et al (2021), showing that the difference might be due to difference in the cassava variety used.…”
Section: Total Phenolscontrasting
confidence: 67%
“…19 Extractions may also be influenced by the variety of the plant, particle size, and plant parts. 90 For instance, the phenolic content was 681.5 and 442.4 GAE mg/100 g in the peel and the stem from the yellow-fleshed cassava variety with a particle size of 0.2 m, respectively. 90 In their study, Gnamien et al (2022) evaluated the energy values, carbohydrate, and starch contents of cassava roots to identify the most favorable harvest and maturity stage that would yield cassava roots with the highest nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…19 Extractions may also be influenced by the variety of the plant, particle size, and plant parts. 90 For instance, the phenolic content was 681.5 and 442.4 GAE mg/100 g in the peel and the stem from the yellow-fleshed cassava variety with a particle size of 0.2 m, respectively. 90 In their study, Gnamien et Table 4.…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation